2018
DOI: 10.1213/ane.0000000000003308
|View full text |Cite
|
Sign up to set email alerts
|

A Device for the Quantification of Oxygen Consumption and Caloric Expenditure in the Neonatal Range

Abstract: This device can measure VO2, VCO2, and EE with sufficient accuracy for clinical decision-making within the neonatal and pediatric size range, including in the setting of tachypnea or hyperoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There are various methods for measuring VO 2 . Indirect calorimetry has long been acknowledgement as a gold standard reference tool [ 14 ]. Mass spectroscopy also enables accurate measurements of VO 2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are various methods for measuring VO 2 . Indirect calorimetry has long been acknowledgement as a gold standard reference tool [ 14 ]. Mass spectroscopy also enables accurate measurements of VO 2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An important source of error in the clinical setting is the use of assumed VO 2 values, rather than direct measurement of VO 2 using mass spectrometry or another reference technique. Nachman et al have demonstrated a new device for clinical measurement of VO 2 in smaller children and infants, using compact engineering and laser‐ and infrared‐based quantification of oxygen and carbon dioxide, respectively. Future integration of such monitoring into anesthesia or intensive care ventilators will allow easy access to VO 2 data.…”
Section: Minimally Invasive Cardiac Output Measurementmentioning
confidence: 99%